Ethanol Production from Sweet Potato by Enzymatic Hydrolyzation and Saccharomyces cerevisiae YRK 017 Fermentation - Ochaikul*, Duangjai Ochaikul1,2*; Suwannaposri, Amornrat (CURRENT APPLIED SCIENCE AND TECHNOLOGY, 2018)
The aim of this work was to utilize sweet potato for production of bioethanol. Optimal conditions of a-amylase and glucoamylase was carried on hydrolyzation of sweet potato and measurement of reducing sugars. The optimal a-amylase concentration and volume were 0.05% (w/v) and 5 ml, respectively at 90°C for 2 h. Using these conditions, the maximum concentration of reducing sugar was 16.43 g L-1. The optimum glucoamylase concentration and volume were 0.015 (w/v) and 20 ml, respectively at 60°C for 4 h. The concentration of reducing sugar was 41.78 g L-1. After hydrolyzation of sweet potato with these two enzymes at optimal condition and fermented using Saccharomyces cerevisiaeYRK 017 (isolated from Loog-pang), the maximum ethanol concentration of 14.55 g L-1 was achieved after 72 h of separate hydrolysis and fermentation process (SHF). For simultaneous saccharification and fermentation process (SSF), the maximum concentration of ethanol was 12.62 g L-1 Keywords: Sweet potato, Saccharomyces cerevisiae, Bioethanol, Simultaneous saccharification and fermentation *Corresponding author: E-mail: kodaungj@kmitl.ac.th